Enhanced Recovery After Surgery Reduces Postoperative Opioid Use and 90-Day Readmission Rates After Open Thoracolumbar Fusion for Adult Degenerative Deformity. Issue 2 (7th September 2020) - Adeyemo, Emmanuel A; Aoun, Salah G; Barrie, Umaru; Nguyen, Madelina L; Badejo, Olatunde; Pernik, Mark N; Christian, Zachary; Dosselman, Luke J; El Ahmadieh, Tarek Y; Hall, Kristen; Reyes, Valery Peinado; McDonagh, David L; et al.
Abstract: BACKGROUND: The role of enhanced recovery after surgery (ERAS) pathways implementation has not been previously explored in adult deformity patients. OBJECTIVE: To determine the impact of ERAS pathways implementation in adult patients undergoing open thoraco-lumbar-pelvic fusion for degenerative scoliosis on postoperative outcome, opioid consumption, and unplanned readmission rates. METHODS: In this retrospective single-center study, we included 124 consecutive patients who underwent open thoraco-lumbar-pelvic fusion from October 2016 to February 2019 for degenerative scoliosis. Primary outcomes consisted of postoperative supplementary opioid consumption in morphine equivalent dose (MED), postoperative complications, and readmission rates within the postoperative 90-d window. RESULTS: There were 67 patients in the ERAS group, and 57 patients served as pre-ERAS controls. Average patient age was 69 yr. The groups had comparable demographic and intraoperative variables. ERAS patients had a significantly lower rate of postoperative supplemental opioid consumption (248.05 vs 314.05 MED, P = .04), a lower rate of urinary retention requiring catheterization (5.97% vs 19.3%, P = .024) and of severe constipation (1.49% vs 31.57%, P < .0001), and fewer readmissions after their surgery (2.98% vs 28.07%, P = .0001). CONCLUSION: A comprehensive multidisciplinary approach to complex spine surgery can reduce opioid intake, postoperative urinary retention and severe constipation, and unplanned 90-d readmissions in the elderly adult population. Graphical Abstract: